Application of E- worksheet Oriented on PBL Model to Improve Critical Thinking Skills on Acid-Base Material - Azizah, Maharani Puspita Nur; Muchlis, Muchlis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Humans often interact with substances containing acids and bases daily. Learning in schools in grade XI, namely in phase F, one of the element achievements that students must complete is that students can use the concept of acids and bases in everyday life. Students are expected to have critical thinking and open minds through scientific work increasingly and, at the same time, strengthen the profile of Pancasila students, especially honest, objective, critical reasoning, creative, independent, innovative, collaborative, and globally diverse. The objective of the research will be to enhance students' critical thinking ability in E-worksheet learning-oriented Problem-Based Learning models within the subject matter of acid and base. The research design used is a descriptive quantitative approach with a pre-experimental design using a